A retrospective study of 68Ga-FAPI PET/CT in differentiating the nature of pulmonary lesions - Xie, Yang; Tang, Wenxin; Ma, Jiao; Chen, Yue (Frontiers in Oncology, 2024)
Purpose: This study aimed to investigate the characteristics of various pulmonary lesions as revealed by 68Ga-FAPI PET/CT and to determine the utility of 68Ga-FAPI PET/CT in distinguishing the nature of these pulmonary lesions. Methods: A retrospective analysis was conducted on 99 patients with pulmonary lesions, who were categorized into three distinct groups: primary lung tumors (G1), metastatic lung tumors (G2), and benign lesions (G3). Each participant underwent a 68Ga-FAPI PET/CT scan. Among these groups, variables such as the Tumor/Background Ratio (TBR), Maximum Standardized Uptake Value (SUVmax), and the true positive rate of the lesions were compared. Furthermore, the FAPI uptake in nodular-like pulmonary lesions (d<3cm) and those with irregular borders was evaluated across the groups. A correlation analysis sought to understand the relationship between FAPI uptake in primary and pulmonary metastatic lesions. Results: The study's participants were composed of 52 males and 47 females, with an average age of 56.8±13.2 years. A higher uptake and detection rate for pulmonary lesions were exhibited by Group G1 compared to the other groups (SUVmax [G1 vs. G2 vs. G3: 9.1±4.1 vs. 6.1±4.1 vs. 5.3±5.8], P<0.05; TBR [G1 vs. G2 vs. G3: 6.2±2.4 vs. 4.1±2.2 vs. 3.2±2.7], P<0.01; true positive rate 95.1% vs. 88% vs. 75.6%]. In nodular-like lung lesions smaller than 3 cm, G1 showed a significantly higher FAPI uptake compared to G2 and G3 (SUVmax [G1 vs. G2 vs. G3: 8.8±4.3 vs. 5.2±3.2 vs. 4.9±6.1], P<0.01; TBR [G1 vs. G2 vs. G3: 5.7±2.7 vs. 3.7±2.1 vs. 3.3±4.4], P<0.05). Both G1 and G2 demonstrated significantly elevated FAPI agent activity in irregular-bordered pulmonary lesions when compared to G3 (SUVmax [G1 vs. G2 vs. G3: 10.9±3.3 vs. 8.5±2.7 vs. 4.6±2.7], P<0.01; TBR [G1 vs. G2 vs. G3: 7.2±2.1 vs. 6.4±1.3 vs. 3.2±2.4], P<0.01). A positive correlation was identified between the level of 68Ga-FAPI uptake in primary lesions and the uptake in pulmonary metastatic lesions within G2 (r=0.856, P<0.05). Conclusion: 68Ga-FAPI PET/CT imaging proves to be of significant value in the evaluation of pulmonary lesions, offering distinctive insights into their nature.